Post-oil farm-based energy: a producer's perspective on anaerobic digestion management - Schaff, Alexander D., author; Román-Muñiz, Noa, advisor; Sharvelle, Sybil, committee member; Engle, Terry, committee member (Colorado State University. Libraries, 2021)
The age of plentiful fossil fuels is reaching its end. This has and will continue to have significant impacts on many aspects of society, particularly agriculture. Renewable energy sources like biofuels provide one of many possible solutions for a transition away from fossil fuels. Anaerobic digestion (AD) is a renewable energy and nutrient management technology that produces biogas, a methane-based gaseous biofuel that can be made from organic wastes, like manure. As the AD industry in the US is relatively underdeveloped compared to the world, this research interviewed twenty dairy farm-based AD operators to uncover the realities of AD in the US, particularly the challenges faced, the solutions found, and the futures envisioned for the industry. Using a survey of both demographic, Likert and open-ended questions, twenty anaerobic digestion operators at grade A dairies were interviewed. After recording and transcribing, the interviews were analyzed quantitatively for discrete answers and qualitatively for themes in the operator's responses. The major themes found were challenges, knowledge, uniqueness, motivators, collaborations, and future. The challenges that arose were related to adoption, pre-digester management, peri-digester management, post-digester management, gas handling and utilities. The most significant motivators were environmental friendliness, zero waste, income incentives, power production, feedstocks, heat for water, automation, bedding, nutrient management, odor control, complementarity of enterprise, and digester friendly environments. The greatest areas of knowledge shared were about the learning process; digester systems; success factors; feeding and feedstocks; PPAs utilities, and RECs; gas and engine management; digestate and bedding management; division of responsibility. Collaborations, unique enterprises, and discussions about the future were notably mentioned. This research demonstrated that AD is a management intensive renewable energy and nutrient management technology. There were three major management categories that arose from the research: 1) feedstock acquisition, and feeding management, 2) biogas and energy production management, and 3) effluent management. This research also showed that while AD technology is often commercialized as a renewable energy technology, the major benefit and challenge to managing these systems is primarily nutrient management. This would suggest that this technology is best conceptualized as a nutrient management technology with the side benefit of renewable energy. Additionally, this research illuminated the fact that while general management categories are the same, each AD system is unique in the solutions to its own challenges. Thus, learning how one's own system works optimally is an imperative to an AD operator's responsibility. That being said, mastering the management categories explored in this research can empower a farm operation to realize the greatest advantages, including generating revenue through tipping fees, and energy generation and crediting systems; displace costs for heat, electricity, bedding, mineral fertilizers; and improving one's nutrient recycling, crop productivity, and neighborly relations.
Keywords: biogas; methane; renewable energy; management; anaerobic digestion; peak oil